Influence of current pulse profile on metal transfer in pulsed gas metal arc welding - Ferreira dos Santos, Emanuel Bruno (University of Waterloo, 2017)
The increase in the requirements of safety and reliability demanded from the normalization institutes by the issue of normalizing standards, led to the need of the development of materials of superior properties. Owing to the development of metallurgy, the development of materials with extremely high values of strength and toughness was made possible. However, employing these materials in industrial applications is limited by the deterioration of their properties after the material is processed using techniques such as welding. To cope with this challenge, several welding process have been developed. One of these processes is the pulse gas metal arc welding (GMAW-P), in which the arc current is periodically pulsed in order to achieve metal transfer and effectively join the material being dealt with, and this decrease the energy input to the base metal. Due to the advance of electronics and transistor technology there are a large number of current pulse profiles commercially available, with different degrees of complexity, designed for specific applications. Determining the balance between the complexity and benefits for the various pulse profiles and process modifications available is the main motivation for the research presented in this thesis. Specifically, the metal transfer of two commercially available current profiles was studied using high-speed imaging and high speed data acquisition of the electrical signal during welding, for different welding conditions. The results showed that the mode of metal transfer differs for the investigated profiles and that for the same pulse profile, as the pulse parameters are modified the metal and heat transfer changes, altering weld bead features such cross-sectional area and penetration.
Keywords: Welding; GMAW; GMAW-P; High Speed Imaging; Metal Transfer; Current Pulse Profile